Evaluation of the changes of interleukin- 6 level in gingival cervical fluid (GCF) during orthodontic movements - Safavi SMR; Farahani M; Khoramian Tusi S; Dianat O; Akbarzade AR (Tehran University of Medical Sciences, 2007)
Background and Aim: In recent years, different substances have been considered in gingival cervical fluid (GCF) as diagnostic markers due to the evaluation of biologic events and biochemical process related to bone turnover during orthodontic movements. IL-6 concentration increases in GCF during the first week after force loading. The aim of this study was to investigate the levels of IL-6 in GCF during orthodontic movements.Materials and Methods: Fourteen orthodontic patients (9 females and 5 males, mean age 15.1±2.5 years) with "nCl I malocclusion needing first bicuspid extraction participated in this clinical trial. In each patient one maxillary canine was distalized (DC) with a NiTi push coil spring. The contra-lateral canine (CC) was included in the orthodontic appliance but was not subjected to the orthodontic force  and one of the mandibular canines was used as control with no orthodontic appliance (Antagonist canine: AC). The concentration of IL-6 was evaluated at the baseline and 14th and 28th days after intervention. GCF was taken with periopapers from both mesial and distal sides of tooth before appliance activation, on the 14th and 28th days. Concentration of IL-6 in DC, CC, and AC detected by ELISA reader was compared by repeated measure ANOVA and LSD multiple comparison, P<0.05 was considered statistically significant.Results: Although the inflammatory gingival indices increased in both DC and CC teeth but it was not significant. The amount of IL-6 in GCF increased on day 14th in DC teeth in comparison with AC and CC teeth. In addition, the concentration of IL-6 in DC teeth was significantly greater than the 1st and 28th days. The maximum concentration of IL-6 was detected in both pressure and tension sides of DCs at T14. At T28, although the IL-6 levels were significantly higher than baseline levels but, it was significantly less than T14.Conclusion: The results of this study support the hypothesis that mechanical stimuli cause an inflammatory reaction within the periodontal tissues.